2014
DOI: 10.1002/cncr.29057
|View full text |Cite
|
Sign up to set email alerts
|

POLE mutations as an alternative pathway for microsatellite instability in endometrial cancer: Implications for Lynch syndrome testing

Abstract: Further elucidation of the genomics of endometrial cancer has the capability and promise of much needed understanding of causative factors of this disease and its hereditary predisposition, development of more effective therapeutics, and improved predictive indicators for use of chemotherapy and radiation therapy. Significant strides toward these goals have been accomplished by The Cancer Genome Atlas (TCGA) project, which has genomically characterized and distilled endometrial cancer into 4 major groups based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 12 publications
(9 reference statements)
0
16
0
Order By: Relevance
“…Although a few cases of POLE MSI-high EC have recently been reported, the majority of previous studies have shown that POLE-mutated EC are microsatellite-stable (MSS) [15, 16]. To evaluate MSI status in POLE-mutated tumor cell lines and whether microsatellite instability may change after prolonged in vitro cultures we tested the tumor tissue blocks and the matched cell blocks of 2 POLE patients for MSI.…”
Section: Resultsmentioning
confidence: 99%
“…Although a few cases of POLE MSI-high EC have recently been reported, the majority of previous studies have shown that POLE-mutated EC are microsatellite-stable (MSS) [15, 16]. To evaluate MSI status in POLE-mutated tumor cell lines and whether microsatellite instability may change after prolonged in vitro cultures we tested the tumor tissue blocks and the matched cell blocks of 2 POLE patients for MSI.…”
Section: Resultsmentioning
confidence: 99%
“…POLE-ultra-mutated tumors account for 7 to 12 % of all endometrial carcinomas (1, 2, 5, 6) and occur secondary to mutations in the exonuclease domain of POLE, a nuclear DNA polymerase endowed with intrinsic proofreading activity (5). Most of POLE-ultra-mutated cancers (including the POLE tumor of patient #1 described above) are MSI stable and cannot be recognized using clinically-approved IHC and PCR-based MSI assays (1, 5, 6). In contrast, hyper-mutated endometrial tumors may occur secondary to different genetic events such as germline mutations in one of the MMR genes (as observed in patients with Lynch syndrome, including patient # 2 above) or because of epigenetic silencing of the promoters of both alleles of the MLH1 gene (1).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, hyper-mutated endometrial tumors may occur secondary to different genetic events such as germline mutations in one of the MMR genes (as observed in patients with Lynch syndrome, including patient # 2 above) or because of epigenetic silencing of the promoters of both alleles of the MLH1 gene (1). Moreover, another group of tumors with MSI phenotype (also referred as “Lynch like” tumors) exist that exhibit loss of expression of 1 or more of the MMR genes secondary to somatic mutations (1, 6). Recent reports analyzing the genetic landscape of endometrial cancers by WES in 232 treatment-naïve endometrial cancer patients (ie, TCGA)(1) and 243 endometrial cancer patients with recurrent disease enrolled in GOG 86P (7) demonstrated that the overall frequency of ultra-mutated and hyper-mutated tumors may range from 35% (ie, 7% POLE, 28% MSI)(1) to 26 % (ie, 2% POLE, 24% MSI)(7), respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Although there is only a weak correlation between the presence of mutations in the exonuclease domain of Pol ε and the decrease of overall survival in MSS colorectal tumors [ 123 ], it was shown that POLE germinal mutations may be responsible for predisposition to colorectal and other cancers, including Lynch syndrome [ 122 , 124 - 126 ]. In endometrial tumors, POLE mutations can play role in the development of microsatellite instability [ 127 ].…”
Section: Mutations In Polymerase Genesmentioning
confidence: 99%